Gold Nanostars-AIE Theranostic Nanodots with Enhanced Fluorescence and Photosensitization Towards Effective Image-Guided Photodynamic Therapy - Yaraki, Mohammad Tavakkoli; Wu, Min; Middha, Eshu; Wu, Wenbo; Rezaei, Soroosh Daqiqeh; Liu, Bin; Tan, Yen Nee (Nano-Micro Letters, 2021)
Dual-functional aggregation-induced photosensitizers (AIE-PSs) with singlet oxygen generation (SOG) ability and bright fluorescence in aggregated state have received much attention in image-guided photodynamic therapy (PDT). However, designing an AIE-PS with both high SOG and intense fluorescence via molecular design is still challenging. In this work, we report a new nanohybrid consisting of gold nanostar (AuNS) and AIE-PS dots with enhanced fluorescence and photosensitization for theranostic applications. The spectral overlap between the extinction of AuNS and fluorescence emission of AIE-PS dots (665 nm) is carefully selected using five different AuNSs with distinct localized surface plasmon (LSPR) peaks. Results show that all the AuNSs can enhance the 1O2 production of AIE-PS dots, among which the AuNS with LSPR peak at 585 nm exhibited the highest 1O2 enhancement factor of 15-fold with increased fluorescence brightness. To the best of our knowledge, this is the highest enhancement factor reported for the metal-enhanced singlet oxygen generation systems. The Au585@AIE-PS nanodots were applied for simultaneous fluorescence imaging and photodynamic ablation of HeLa cancer cells with strongly enhanced PDT efficiency in vitro. This study provides a better understanding of the metal-enhanced AIE-PS nanohybrid systems, opening up new avenue towards advanced image-guided PDT with greatly improved efficacy. Highlights: 1 Development of Au nanostar@AIE nanodots photosensitizers for theranostic applications. 2 Achieving excellent metal-enhanced fluorescence and singlet oxygen generation efficiency simultaneously. 3 Mechanism study of the role of FRET on metal-enhanced singlet oxygen generation.